Refusal in activities in situations of failure as a manifestation of professional burnout of managers (Actual Problems of Psychology in Educational Institutions, 2021)
The article presents the results of comparative studies of theintensity of burnout syndrome in the group of managers. The Polish versionof the AVEM Questionnaire for Behavior and Experience (ArbeitsbezogenesVerhaltens- und Erlebensmuster, Schaarschmidt, Fischer, 1997) in thePolish adapted version (Rongi´nska, Gaida, 2012) was used in the research.Particular attention was paid to overcoming behavior in a situation offailure, and refusal to work is seen as a leading condition for the rapiddevelopment of symptoms of professional burnout. The main componentsof the syndrome were selected, especially the lack of ability to cope withfailure as an important reason for the rapid development of symptoms.The possibilities of preventing burnout syndrome focused on strengtheningthe ability to cope with failure mainly for people striving for perfectionare presented.